2013
DOI: 10.1158/0008-5472.can-12-2218
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Regulation of miR-21 Enhances Migration and Invasion of Hepatoma

Abstract: Thyroid hormone (T 3 ) signaling through the thyroid hormone receptor (TRa1) regulates hepatoma cell growth and pathophysiology, but the underlying mechanisms are unclear at present. Here, we have shown that the oncomir microRNA-21 (miR-21) is activated by T 3 through a native T 3 response element in the primary miR-21 promoter. Overexpression of miR-21 promoted hepatoma cell migration and invasion, similar to that observed with T 3 stimulation in hepatoma cells. In addition, anti-miR-21-induced suppression of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 48 publications
3
35
0
1
Order By: Relevance
“…Thyroid hormone (T3) increased transcript levels of both miR-21 and the TMEM49/VMP1 gene in which it is encoded in HepG2 cells stably overexpressing thyroid hormone receptor ␣1 (TR␣1) or TR␤1 (25). IL-6 was reported to increase miR-21 in normal human hepatocytes by activating Stat3 recruitment to the miR-21 promoter (21).…”
mentioning
confidence: 99%
“…Thyroid hormone (T3) increased transcript levels of both miR-21 and the TMEM49/VMP1 gene in which it is encoded in HepG2 cells stably overexpressing thyroid hormone receptor ␣1 (TR␣1) or TR␤1 (25). IL-6 was reported to increase miR-21 in normal human hepatocytes by activating Stat3 recruitment to the miR-21 promoter (21).…”
mentioning
confidence: 99%
“…The tumor cells then extravasate and colonize into a macrometastasis 12 . Progression through the epithelial to mesenchymal transition (EMT), tumor invasion, and metastasis has been enhanced by steroid hormones 13,14 , growth factors [15][16][17][18] , and cytokines [19][20][21] . These molecules are so critical to addressing the signaling pathway of tumor progression, that the development of an assay to address their role in tumor invasive potential is an important step toward deciphering the intricate signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, other studies have demonstrated that T 3 treatment of the same cells leads to spondin 2 overexpression, which inhibits cell invasion and migration (Liao et al 2010). T 3 treatment also upregulates the expression of DKK4 protein, an antagonist of Wnt, in HepG2 TR-expressing cells (Chi et al 2013), suggesting that the T 3 upregulation of the TR/DKK4/Wnt/β-catenin cascade inhibits the metastasis of hepatoma cells (Liao et al 2012).…”
Section: Tissue Invasion and Metastasismentioning
confidence: 95%
“…T 3 -induced cell migration in HCC is mediated in part to a reduction in miR-17 and miR-130b expression (Lin et al 2013b and the overexpression of miR-21 (Huang et al 2013). The overexpression of miR-17 markedly inhibits HCC cell migration and invasion in vitro and in vivo via the suppression of MMP-3 (Lin et al 2013b), whereas the effect of miR-130b involves the regulation of genes critical for metastasis, such as MMP-9, mTOR, ERK1/2, AKT and STAT-3 .…”
Section: Tissue Invasion and Metastasismentioning
confidence: 99%